(untitled) (Journal of Asian Development Studies, 2024)
Displacement forces communities to shift their habitat which may also affect their socio-economic status. Very few scholarly studies documented its socio-economic impacts. Especially the impacts of forced internal displacement resulting from the development of new housing societies are missing in the literature. To fill the gap, the present study aims to explore the socio-economic impacts of internal displacement on villagers displaced from three villages of Lahore. For this purpose, 18 in-depth interviews were conducted through purposively sampling. Qualitative methodology and methods were used to achieve the research objectives, to select and recruit the research participants and to collect and analyze data. Internal forced displacement negatively affected the daily routine activities, social capital, and breakdown in the family system, detachment and identity crises and sense of community ownership. Displacement also generated economic dependence among villagers and made their skills and expertise non-relevant in relocated settings. Hence, proper resettlement policy and plans are advised to be implemented before displacement to avoid its negative socio-economic impacts